O mandonismo local e a política no sertão da Bahia : o caso do município de Paripiranga - Carregosa, Antonio Santana (2015)
This thesis examines the changes and continuities in local politics in the city of Paripiranga (BA). The database was established from documentary and statistical survey, interviews and participant observation. The survey found that the power of command in the city has changed over time with a view to the progressive cooling of the oligarchic structure and the traditional type of relations. With the process of democratization and the subsequent political changes the old factions fragmented, new characters and new forms of political mediation emerged into existence a better balance between institutions and political elites. However, the political culture still maintains many of its old brands, which is more evident in the municipal elections, while still occurs the clash between two political poles (the opposition and the situation) based on various forms of election as grooming, for example, the "vote buying" and the use of physical violence. Thus, the thesis concludes that the socioeconomic and political-institutional changes that occurred in Brazil and Bahia in recent decades have caused cracks in the local despotism and become more complex and multifaceted policy, even in small hinterland municipalities. However, in these contexts, which have a history of oligarchic domination and predominance of social relations of traditional type, these changes are adjusted and re-signified by setting up a process with changes and continuities.